HAZARD EXAMINATION OF AMMONIA UNIT CONVERTER IN FERTILIZER INDUSTRY UTILIZING HAZOP STRATEGY - Riny Yolandha Parapat; Windy Nur Ramadhani Putri Hidayat, Helmi Sayid Hasan, Aditya Raka Fadhilla (ADISAM PUBLISHER, 2026)
Hazard Framework, Hazard Administration, HAZOP, Ammonia Converter, Hazard Examination, Ammonia Plant This ponder assesses the security and operational dangers of the smelling salts converter unit in an smelling salts generation plant utilizing the Danger and Operability Consider (HAZOP) technique. The investigation recognized a few potential dangers, counting moo weight within the converter due to limited channel stream, tall temperature at the gas burner coming about from broken tubes, and moo temperature during the change prepare that will diminish ammonia transformation productivity. Extra issues were watched in supporting units, such as overpressure within the compressor and no stream within the refrigeration framework. These deviations might lead to decreased item surrender, catalyst wastefulness, hardware disappointment, or indeed major security episodes. The think about suggests remedial activities such as controlling gulf stream rates, executing interlock frameworks, conducting schedule reviews, and moving forward temperature and stream observing. These discoveries offer profitable experiences into moving forward the unwavering quality, security, and proficiency of ammonia converter operations and give a organized system for risk moderation in comparative high-risk chemical forms.